Co-constructing a Liberated / Decolonised Arts Curriculum - Crilly, Jess; Panesar, Lucy; Suka-Bill, Zey (Journal of University Teaching and Learning Practice, 2020)
This article presents a case study of liberating reading lists through a staff-student collaboration in a UK arts university. It characterizes reading lists as a familiar but under researched feature of academic life and discusses their practical and symbolic role in maintaining Western / Eurocentric / White disciplinary canons, and how they inform what it means to be ‘well read’ in a discipline. The collaborative project, which was initiated as Liberate the Curriculum work, brought together students, academic staff and librarians to audit and review reading lists, and reimagine them to represent multiple narratives, reflecting the diverse and international student population of the university. The article explores the challenges of auditing reading lists and identifying more diverse resources, and the complex relationships between identity and knowledge production. The authors use Critical Race Theory to comment on the relationship between race, colonialism and the arts, and how racism is reproduced within the academic environment. The project methodology is described, with an evaluation of the project as a student staff collaboration, and the learning and impact within the institution.